Digital or Sad Poetry: The Enthusiasm over Sadness on Wattpad - Mauludi, Anugrah Bulan; Afdholy, Nadya; Setijowati, Adi (LPPM Universitas Bina Sarana Informatika, 2025)
Despite indicating the development of literature in a modern world, Wattpad allows any type of influence to enter its platform. Many people are under the age of adulthood, but they are writing popular poems. Wattpad’s poetry itself has many images related to sadness. This research aims to study enthusiasm over sadness in Wattpad’s poetry. The method was based on a qualitative-quantitative mixed method. It is found that the images of sadness revolve around guilt, depression, loneliness, trauma, and betrayal. Based on the qualitative approach, findings show that depression’s image gets portrayed more than the rest. This article proposes to conduct a study of Wattpad literature based on popular works and also to use a qualitative approach to investigate the content of the platform itself. The neutrality of Wattpad’s comments is considered non-canonical from a quantitative sentiment analysis point of view and, therefore, requires greater attention for future research.